Mengurangi Perilaku Merokok Siswa melalui Konseling Pendekatan REBT dengan Teknik Time Projection - bachtiar, ganang; sugiyo, sugiyo (Universitas Negeri Semarang, 2016)
This study was conducted based on the phenomenon that occurs in students at SMP N 2 Jaken which has a high smoking behavior. The purpose of this study was to investagate tingat smoking behavior of students before and after counseling services as well as the effectiveness of the counseling approach rational emotive behavior therapy time projection techniques in reducing smoking behavior of students. This type of research is experimental research. Experimental research is research used to seek treatment effect tenterntu. This research carried out with 5 times the provision of treatment to students with a number of research subjects 2 students. Data collection method used is the psychological scale, observation, and interviews. Data were analyzed using analysis deskiptif percentage and Wilcoxon test. The results showed the smoking behavior in the high category R1 (69.5%) and R2 (68%). After being given treatment decline in smoking behavior in the low category R1 (55.5%) and R2 (55%). It shows that the smoking behavior of students can be lowered to 2 with counseling approach rational emotive behavior therapy time projection technique.